Primary structure and mapping of the hupA gene of Salmonella typhimurium. - Higgins, N P (1988)
In bacteria, the complex nucleoid structure is folded and maintained by negative superhelical tension and a set of type II DNA-binding proteins, also called histonelike proteins. The most abundant type II DNA-binding protein is HU. Southern blot analysis showed that Salmonella typhimurium contained two HU genes that corresponded to Escherichia coli genes hupA (encoding HU-2 protein) and hupB (encoding HU-1). Salmonella hupA was cloned, and the nucleotide sequence of the gene was determined. Comparison of hupA of E. coli and S. typhimurium revealed that the HU-2 proteins were identical and that there was high conservation of nucleotide sequences outside the coding frames of the genes. A 300-member genomic library of S. typhimurium was constructed by using random transposition of MudP, a specialized chimeric P22-Mu phage that packages chromosomal DNA unidirectionally from its insertion point. Oligonucleotide hybridization against the library identified one MudP insertion that lies within 28 kilobases of hupA; the MudP was 12% linked to purH at 90.5 min on the standard map. Plasmids expressing HU-2 had a surprising phenotype; they caused growth arrest when they were introduced into E. coli strains bearing a himA or hip mutation. These results suggest that IHF and HU have interactive roles in bacteria.